The effect of thiamine pyrophosphate on ethambutol-induced ocular toxicity. (2nd July 2016) - Cinici, Emine; Cetin, Nihal; Ahiskali, Ibrahim; Suleyman, Bahadir; Altuner, Durdu; Alp, Hamit Hakan; Sener, Ebru; Calik, Ilknur; Suleyman, Halis
Abstract: Context : Ethambutol-induced retinal oxidative damage in patients with tuberculosis is still not being adequately treated. The protective effect of thiamine pyrophosphate against oxidative damage in some tissues has been reported, but no information on the protective effects of thiamine pyrophosphate against ethambutol-induced oxidative retinal damage has been found in the medical literature. Objective : The objective is to investigate whether thiamine pyrophosphate has a protective effect against oxidative retinal damage in rats induced by ethambutol. Materials and methods : Experimental animals divided into four groups ( n  = 10): the healthy group (HG), the ethambutol control group (EMB), thiamine + ethambutol group (Thi–EMB) and thiamine pyrophosphate + ethambutol group (TPP–EMB). The rats in the TPP–EMB and Thi–EMB groups were administered thiamine pyrophosphate and thiamine, respectively, at doses of 20 mg/kg intraperitoneally. Distilled water was administered intraperitoneally to the HG and the EMB groups as a solvent in the same volumes. One hour after drug injection, 30 mg/kg ethambutol was administered via an oral gavage to the TPP–EMB, Thi–EMB and EMB groups. This procedure was repeated once a day for 90 days. At the end of this period, all rats were euthanized under high-dose thiopental sodium anesthesia, and biochemical and histopathological investigations of the retinal tissue were performed. Results : Malondialdehyde (MDA) and DNA damage product 8-hydroxyguanine levels were significantly lower in the retinal tissue of TPP–EMB and HG groups compared to those of the Thi–EMB and EMB groups, and total glutathione (tGSH) was also found to be higher. In addition, severe retinal tissue vascularization, edema and loss of ganglion cells were observed in the Thi–EMB and EMB groups, whereas histopathological findings for the TPP–EMB group were observed to be close to normal. Discussion and conclusion : These findings suggest that thiamine pyrophosphate protects retinal tissues from ethambutol-induced oxidative damage, and thiamine does not. This positive effect of thiamine pyrophosphate may be useful in the prevention of ocular toxicity that occurs during ethambutol use.